1964
DOI: 10.1111/j.1365-2621.1964.tb01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Flavor and Odor Precursors of Meat. I. Qualitative Study of Certain Amino Acids, Carbohydrates, Non‐Amino Acid Nitrogen Compounds, and Phosphoric Acid Esters of Beef, Pork, and Lamba

Abstract: SUMMARY Paper and ion‐exchange chromatography were used to determine qualitatively certain constituents in lyophilized diffusates from cold‐water extracts of beef, lamb, and pork muscles. The qualitative contents of low‐molecular‐weight diffusible organic constituents in tissue from these three species were remarkably similar. Involvement of constituents studied as flavor and odor precursors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…The concentrations of free cysteine (range of values for individual animals 0.02-0.06 mg/100 g) and free methionine (1.3-2.1 mg/ 100 g) were lower than values recorded in the literature for most meat types, since the concentration of free methionine found in meat is typically 2-6 mg/100 g, while cysteine ranges from 0.03 to 2.1 mg/100 g. In fact, there were very few literature measurements of cysteine in meat; the early papers reported an absence or the presence of only a trace amount (Jarboe & Mabrouk, 1974;Macy et al, 1964aMacy et al, , 1964b, as its concentrations are very low in meat.…”
Section: Free Amino Acidsmentioning
confidence: 68%
See 1 more Smart Citation
“…The concentrations of free cysteine (range of values for individual animals 0.02-0.06 mg/100 g) and free methionine (1.3-2.1 mg/ 100 g) were lower than values recorded in the literature for most meat types, since the concentration of free methionine found in meat is typically 2-6 mg/100 g, while cysteine ranges from 0.03 to 2.1 mg/100 g. In fact, there were very few literature measurements of cysteine in meat; the early papers reported an absence or the presence of only a trace amount (Jarboe & Mabrouk, 1974;Macy et al, 1964aMacy et al, , 1964b, as its concentrations are very low in meat.…”
Section: Free Amino Acidsmentioning
confidence: 68%
“…They suggested that the components contributing to the development of the characteristic species-specific flavours and aromas are located in the lipid fraction, while the water-soluble fraction contains components, which contribute to the development of 'meaty' aroma. Macy, Naumann, and Bailey (1964a) verified the presence of glucose, fructose, mannose and ribose in meat, and determined the ribose, glucose and fructose content of beef, lamb and pork muscle, before and after heat treatment (Macy, Naumann, & Bailey, 1964b). They concluded that ribose was the most heat-labile sugar, while fructose was the most stable.…”
Section: Introductionmentioning
confidence: 96%
“…115-130 °C) the loss was apparently independent of the presence of fat (Lea et al [9]). However, Macy et al [10] found that most free amino acids increased in concentration during cooking of roasts to an internal temperature of 77 °C with the exception of threonine, serine, glutamic acids, histidine and arginine. They attributed this general increase in amino acids content to hydrolysis of protein by proteolyttic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Однако, Macy et al [10] установили, что кон-центрации большинства свободных аминокислот уве-личивались при термообработке порционных кусков для жарки до достижении температуры в центре куска 77 °C за исключением треонина, серина, глутаминовой кислоты, гистидина и аргинина. Общее увеличение содержания аминокислот объясняется гидролизом Alfaia et al [3] found the heating time, temperature, cooking method and muscle composition to be the important variables, which may influence the final desirable characteristics of meat.…”
Section: Introductionunclassified
“…ter)는 유리래디칼(free radicals) 소거 능력을 가지고 있는 대표적인 기능성 생리물질이다 (Arduini, 1992 유리아미노산 및 핵산과 같은 저분자 수용성 물질은 고 기의 맛과 향기에 기여하는 중요한 전구물질이다 (Mancy et al, 1964). 이중 유리아미노산은 단맛, 신맛, 쓴맛, 짠맛 및 우마미(umami)에 직접적으로 관여할 뿐만 아니라 (Kato et al, 1989), glucose, glucose 5-phosphate, ribose, ribose 5-phosphate 등과 같은 당류와 메일라드(maillard) 반응물을 생성하여 가열육 특유의 향기를 생성하기도 한다 (Cerny and Grosch, 1994).…”
unclassified